Who becomes a teacher? Challenging the "negative selection" hypothesis. (April 2015) - Roloff Henoch, Janina; Klusmann, Uta; Lüdtke, Oliver; Trautwein, Ulrich
Abstract: Previous findings on teacher candidates' characteristics seem to support the assumption of a "negative selection" into the teaching profession, with teacher candidates showing less favorable individual characteristics than students in other subject areas. Against the background of current concerns about the supply of high-quality teachers, particularly in the field of science, technology, engineering, and mathematics (STEM), the present research used longitudinal data from more than 1400 students in Germany to compare teacher candidates' demographic, cognitive and personality characteristics with those of students in other subject areas. The study overcomes limitations in prior studies in that it (1) assessed personal characteristics before study entry in order to exclude "contamination" effects, (2) selected an appropriate control group, and (3) differentiated between STEM and non-STEM study majors. The results did not find any empirical support for the negative selection hypothesis in terms of cognitive and personality characteristics in Germany. Instead, vocational interests (especially social interests) emerged as the most important predictor of the enrollment in a teacher education program. Highlights: We investigate teacher candidates' cognitive and personality characteristics. Use of longitudinal data and differentiation between different study majors. No empirical support for the "negative selection" into teacher education hypothesis. Vocational interests (esp. social) as important predictor for choice of teaching.